Design of bow-tie patch antenna with slot to improve the performance at 2.5GHz: article / I'Faf Mohd Rodhi - Mohd Rodhi, I'Faf (2016)
This paper presents a design of bow-tie antenna with a rectangular-shape slot on the patch for wireless application. The investigation was carried out with two different design that is a conventional bow-tie antenna and bow-tie antenna with slot on the patch.